Answer:
(x +6 ) ( x- 6)
Step-by-step explanation:
Answer: ![B. \: \: \: \dfrac{5}{x+5}](https://tex.z-dn.net/?f=B.%20%5C%3A%20%5C%3A%20%5C%3A%20%5Cdfrac%7B5%7D%7Bx%2B5%7D)
Step-by-step explanation:
![\dfrac{\dfrac{1}{x+5} }{\dfrac{x+3}{5x+15} } =\dfrac{1}{x+5} \times \dfrac{5x+15}{x+3}=\dfrac{1}{x+5} \times \dfrac{5(x+3)}{x+3}=\dfrac{1}{x+5} \times 5 = \dfrac{5}{x+5}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cdfrac%7B1%7D%7Bx%2B5%7D%20%7D%7B%5Cdfrac%7Bx%2B3%7D%7B5x%2B15%7D%20%7D%20%3D%5Cdfrac%7B1%7D%7Bx%2B5%7D%20%5Ctimes%20%5Cdfrac%7B5x%2B15%7D%7Bx%2B3%7D%3D%5Cdfrac%7B1%7D%7Bx%2B5%7D%20%5Ctimes%20%5Cdfrac%7B5%28x%2B3%29%7D%7Bx%2B3%7D%3D%5Cdfrac%7B1%7D%7Bx%2B5%7D%20%5Ctimes%205%20%3D%20%5Cdfrac%7B5%7D%7Bx%2B5%7D)
5x - y = 3 ------------ (1)
6x - y = 8 ------------ (2)
From (1):
5x - y = 3
y = 5x - 3 ------------ Sub into (2)
6x - (5x - 3) = 8
6x - 5x + 3 = 8
x + 3 = 8
x = 5 ------------------- Sub into (1)
5x - y = 3
5(5) - y = 3
25 - y = 3
y = 25 - 3
y = 22
---------------------------------
Ans: x = 5, y = 22
---------------------------------